Global Research Trends on the ADDIE Development Model in Mathematics Education: A Bibliometric Analysis - Kristiawan, Yusie; Suparman, Suparman (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Education plays an important role in creating quality human resources, especially in mathematics learning which is often considered challenging. The development of relevant open devices is the main solution to improve the quality of learning. This article reviews the use of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model in the development of mathematics teaching devices. This model offers a systematic and iterative framework for designing contextual and interactive learning. The study used the PRISMA framework for systematic observation of 32 articles published in 2014-2024, covering publication distribution, ADDIE implementation in various contexts, and global trends in teaching device development. The results show that ADDIE is widely applied, adjusted to local needs, such as technology integration in developed countries and minimal resource approaches in developing countries. This model has been shown to improve student learning outcomes, although challenges such as time and resource constraints remain. The study recommends optimizing ADDIE for student-based learning innovations.